Pengaruh Pemberian Pupuk Kompos Daun Pisang (Musa Paradisiaca L) Terhadap Pertumbuhan Tinggi Tanaman Sawi Hijau (Brassica Juncea L) - Halisah Suriani (Departement of Mathematics Education, 2023)
This study aims to determine whether there is an effect of applying banana leaf compost (Musa paradisaca L) on the growth of mustard greens (Brassica juncea L). This research was conducted at the Biology Laboratory of the teaching and education faculty, Gunung Leuser University, UGL Aceh in march 2023. It was a nonfactorial complete randomized design experiment (CRD) with 3 replications and 5 treatments, with samples of mustard greens (Brassica juncea L) and banana leaf compost (Musa paradisaca L). Parameters observed were height of the leaf sheath (cm) of mustard greens measured after 7 days, 14 and 21 days of plant age. Based on the result of the study at the age of 7 days after planting, the height of the leaf midrib did not show a significant effect because the calculated F value < F table (0,42 < 4,53) and so also at the age of 14 days after planting there was no significant effect because the calculated F value < F table (1,50 < 4,53). Then on the 21st day after the new planting there is a significant effect this because the calculated F value > F table (5,64 > 4,53). The results of the data analysis showed that there was ab effect of applying banana leaf compost (Musa paradisaca L) on the growth of mustard greens (Brassica juncea L).